(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the phytochemical composition and antimicrobial potency of a methanolic root fraction from Vitellaria paradoxa, a plant widely utilized in traditional medicine. Through TLC analysis, multiple fractions with distinct Rf values were identified, indicating a diverse chemical profile. Both the crude extract and its fractions demonstrated significant bacteriostatic activity against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Salmonella typhi, with the F1 fraction (Rf 0.33) showing the highest potency (MIC of 6.25 mg/ml against most tested bacteria). Qualitative and quantitative phytochemical screening confirmed the presence of various bioactive compounds, notably high concentrations of phenols (9.73 mg/g) and tannins (7.44 mg/g), alongside flavonoids, alkaloids, and saponins. These findings validate the traditional use of V. paradoxa roots and highlight its potential as a source of novel antimicrobial agents to combat escalating drug resistance.